1993
DOI: 10.1366/0003702934065993
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Investigation of Fluorescence Quenching Agents. Part IV: Selectivity of Nitromethane for Discriminating between Alternant versus Nonalternant Polycyclic Aromatic Hydrocarbons in Solvents of Differing Polarities

Abstract: To further assess the applicability of nitromethane as a selective quenching agent for alternant vs. nonalternant polycyclic aromatic hydrocarbons in HPLC analysis, we measured the effect that it has on the fluorescence emission behavior of 96 different polycyclic aromatic hydrocarbons dissolved in a binary ethyl acetate/acetonitrile solvent mixture. Nitromethane quenching results are compared with previously reported acetonitrile, aqueous/acetonitrile, and toluene/acetonitrile solvent mixtures. Results of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1996
1996
2003
2003

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Initial work by Sawicki and co-workers showed that nitromethane, an electron acceptor, selectively deactivated the fluorescence of alternant PAHs A quantitative study by Ogasawara and co-workers revealed that the quenching constants of nitromethane were 33−100 times greater for alternant PAHs than for their nonalternant isomers. , The closely related molecule nitrobenzene was found to be a more efficient quencher than nitromethane but lacked any useful selectivity . Zander and co-workers reported that 1,2,4-trimethoxybenzene, an electron donor, selectively deactivated the fluorescence of nonalternant PAHs .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Initial work by Sawicki and co-workers showed that nitromethane, an electron acceptor, selectively deactivated the fluorescence of alternant PAHs A quantitative study by Ogasawara and co-workers revealed that the quenching constants of nitromethane were 33−100 times greater for alternant PAHs than for their nonalternant isomers. , The closely related molecule nitrobenzene was found to be a more efficient quencher than nitromethane but lacked any useful selectivity . Zander and co-workers reported that 1,2,4-trimethoxybenzene, an electron donor, selectively deactivated the fluorescence of nonalternant PAHs .…”
mentioning
confidence: 99%
“…17 Subsequent systematic studies by Acree and co-workers demonstrated that this so-called "nitromethane selective quenching rule" was broadly applicable with only a few exceptions. [18][19][20][21][22] A quantitative study by Ogasawara and co-workers revealed that the quenching constants of nitromethane were 33-100 times greater for alternant PAHs than for their nonalternant isomers. 23,24 The closely related molecule nitrobenzene was found to be a more efficient quencher than nitromethane but lacked any useful selectivity.…”
mentioning
confidence: 99%